Predictors of internal auditor's intention to whistleblow in Malaysian public listed companies: a planned behaviour approach / Nur Syazwin Preshahdin - Preshahdin, Nur Syazwin (2019)
This study focuses on the internal auditor's intention to whistleblow in Malaysian Public Listed Companies. The purpose of this study is to examine the predictors of internal auditor's intention to whistleblow in Malaysian Public Listed Companies and had adopted the theory of planned behaviour. Whistleblowing is the act of reporting any wrongdoing to the responsible parties. Whistleblowing plays an important role for the internal control system in the company to encourage good corporate governance. There are four variables involved in this study which are the internal auditor's intention to whistleblow (Dependent Variable), attitude (Independent Variables 1), subjective norms (Independent variable 2), and perceived behavioural control (Independent Variables 3). In order to collect data from respondents, systematic random sampling technique had been used as the sampling technique. In this study, the researcher used quantitative method and had distributed 395 set of questionnaires by hand and also had emailed the targeted respondents who were the internal auditors. Of this 395 questionnaire, only 274 were returned within the time frame of data collection. SPSS software was used to analyse data retrieved from the questionnaires. The finding of this research study shows that the internal auditors had the intention (DV) and were willing to whistleblow any wrongdoing in the companies with the mean value of 4.0253. Then, the variables of attitude and subjective norms have positive impacts toward the intention of internal auditor to whistleblow in the company. Meanwhile, this study discovered the perceived behavioural control has no effect towards the intention of internal auditor to whistleblow in the company. This study also found that the main factor that influenced the intention of internal auditor to whistleblow is the attitude. The overall findings of this study will provide some ideas for future researchers to further investigate the whistleblowing practices that will lead towards good corporate governance in the company.